2021
DOI: 10.1038/s41467-021-20966-2
|View full text |Cite
|
Sign up to set email alerts
|

Deep convolutional neural networks to predict cardiovascular risk from computed tomography

Abstract: Coronary artery calcium is an accurate predictor of cardiovascular events. While it is visible on all computed tomography (CT) scans of the chest, this information is not routinely quantified as it requires expertise, time, and specialized equipment. Here, we show a robust and time-efficient deep learning system to automatically quantify coronary calcium on routine cardiac-gated and non-gated CT. As we evaluate in 20,084 individuals from distinct asymptomatic (Framingham Heart Study, NLST) and stable and acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
89
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(94 citation statements)
references
References 52 publications
(61 reference statements)
4
89
0
1
Order By: Relevance
“…Our model uses a single convolutional neural network (CNN) for an end-toend approach. Most significantly, all deep learning models 26,28,29,31,32 on CAC scoring using non-gated unenhanced chest CTs reported to date have used manual scoring on non-gated chest CTs solely as the reference standard, which may be inadequate. Most notably, a recent study by Zeleznik et al 32 demonstrated substantial agreement between automated and manual stratification of CAC scores into one of four risk buckets in a multi-center trial cohort comprised of over 20k asymptomatic individuals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our model uses a single convolutional neural network (CNN) for an end-toend approach. Most significantly, all deep learning models 26,28,29,31,32 on CAC scoring using non-gated unenhanced chest CTs reported to date have used manual scoring on non-gated chest CTs solely as the reference standard, which may be inadequate. Most notably, a recent study by Zeleznik et al 32 demonstrated substantial agreement between automated and manual stratification of CAC scores into one of four risk buckets in a multi-center trial cohort comprised of over 20k asymptomatic individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Most significantly, all deep learning models 26,28,29,31,32 on CAC scoring using non-gated unenhanced chest CTs reported to date have used manual scoring on non-gated chest CTs solely as the reference standard, which may be inadequate. Most notably, a recent study by Zeleznik et al 32 demonstrated substantial agreement between automated and manual stratification of CAC scores into one of four risk buckets in a multi-center trial cohort comprised of over 20k asymptomatic individuals. However, the comparison here was also made to manual quantitation performed on non-gated studies as opposed to the current standard of care to quantify CAC, a gated coronary CT exam.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…van Velzen et al used DL to identify and quantify calcium on CT using 7240 participants, which included ECG-gated CT, diagnostic CT of the chest, PET attenuation correction CT, radiotherapy planning CT, and low-dose screening CT for lung cancer [ 51 ]. The resulting model had an intraclass correlation coefficient of 0.85–0.99 for the identification of CAC, leading to the prospect of routine automated quantification of calcification on thoracic CT. More recently, a study using 20,084 gated and non-gated cardiac CT scans developed a deep learning model to identify coronary calcification with excellent correlation with manual readers (r 0.92, p < 0.001) and test-retest stability (intra-class correlation 0.993, p < 0.001) [ 52 ].…”
Section: Ai In Cardiovascular Ctmentioning
confidence: 99%